Plastic hinge rotations of steel braces estimated using improved physical theory models. (April 2023) - Shin, Dong-Hyeon; Kim, Hyung-Joon
Abstract: The cyclic response of a typical steel brace cannot be easily captured due to its asymmetric force-deformation relation due to buckling resulting in substantially strength deterioration. Regardless of experimental and analytical efforts on the behavior of steel braces, current physical theory models overestimate their compression strengths after buckling. This study first reviewed the formulations employed in the current physical theory model and then carried out full scale cyclic tests of W-shaped steel braces to find out and to expose problems of the current physical theory model. The tests show that plastic hinge rotations from the maximum tensile strength to the maximum compressive strength are not maintained, which does not agree with the underlying assumption of the current physical theory model. This paper suggests the improved model that can employ a new finding on the behavior of plastic hinges at buckled steel braces. It was confirmed from the validation that the improved model with a nonlinear assumption can properly capture the changes of hinge rotations during the excursion between the maximum tensile and compressive loads and can be the best candidate for addressing the shortcoming of the existing physical theory model. Highlights: To propose an improved physical theory model to simulate hysteretic behavior of steel braces. To review the formulations employed in the current physical theory model. The simplified relations are developed to simulate variation of plastic hinge rotations.